Isu-isu alam sekitar di Malaysia menurut pandangan pakar: satu analisis perbandingan berdasarkan tafsir Al-Misbah / Imaaduddin Abdul Halim - Abdul Halim, Imaaduddin (Universiti Teknologi MARA, Sabah, 2020)
Recently, there are various environmental issues in Malaysia that attract interests to many parties. These issues involved various aspects of environmental including pollution, exploitation of natural resources and attitude of the people themselves. To sum it up, these issues stem from the human behavior itself. With the development of advanced technology, there are many requests to use these natural resources to produce various equipment and things. Exploitation of greedy people also has worsened this environmental issue. As a result, there are many consequences and effects whether in land, water and air. Accordingly, this problem also causes many problems such as natural disasters, damage the earth's ecosystem and human health. From the perspective of Islam which Qur'an as an absolute reference, the guidance is able to avoid the destruction of this environment if everybody knows their responsibility and trust as caliph on this earth. The main objective of this article to analyze the experts’ views and compare it’s to M. Quraish Shihab in Tafsir al-Misbah. Based on the content analysis methodology and the unstructured interview, the findings show that the experts views are in line with the tafsir al-Misbah.